Pengaruh Brand Image dan Relationship Marketing Terhadap Loyalitas Pelanggan Pada Coffee Shop Kopi Petik Pancur Batu Kabupaten Deli Serdang - Vinolia, Gladys; Wijaya, Muslim (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The purpose of this study is to determine the effect of Brand Image and Relationship Marketing on Customer Loyalty at Kopi Petik Pancur Batu Coffee Shop in Deli Serdang Regency. This study uses a quantitative approach where the population in this study are customers of the Kopi Petik Pancur Batu brand in Deli Serdang Regency, selected using purposive sampling. Data collection was conducted through questionnaires. The results of the study show that Brand Image (X1) has a positive influence with a coefficient value (β1) of 0.537 and a significant effect on Customer Loyalty with a value of (0.000) < 0.05. then the Relationship Marketing variable (X1) has a positive effect with a Coefficient value (β2) of 0.191 and has a significant effect on Customer Loyalty with a value of (0.005) < 0.05. The results also show that Brand Image and Relationship Marketing simultaneously have a significant effect on Customer Loyalty with an F-value of 353.145 > F-table 2.69. The tests conducted show that Brand Image and Relationship Marketing partially have a positive and significant effect on Customer Loyalty. The Adjusted R Square value obtained from the Determinant Coefficient (R2) test on customer loyalty was 0.877, meaning that 87.7% can be explained by Brand Image and Relationship Marketing. Meanwhile, the remaining 12.3% can be explained by other factors not examined in this study